An Early Cretaceous zamiaceous cycad of South West Gondwana: Restrepophyllum nov. gen. from Patagonia, Argentina - Passalia, Mauro Gabriel (2010)
The record of Cycadales in Patagonia begins in the Triassic and extends up to the Oligocene. In this region the group is highly diversified and includes several taxa represented by trunks, leaves and pollen cones. A new cycadalean genus and species, Restrepophyllum chiguoides, form the Aptian Anfiteatro de Ticó Formation, Santa Cruz province, Argentina, is described here. The fossil is a leaf compression with well-preserved cuticle. Its morphology, anatomy and ultrastructure are studied by means of light and electron microscopy. The leaf is lanceolate, serrate, and possesses a prominent midvein and decurrent laterals showing an open, simple or dichotomous venation. The leaf is hypostomatic, and the abaxial cuticle is thinner than the adaxial one. The stomata are irregularly distributed and indistinctly oriented between veins. They are monocyclic to imperfectly dicyclic (haplocheilic); the suprastomatal aperture is raised over the epidermis and the guard cells are sunken. Scattered trichomes and crystalliferous idioblasts are also present. The cuticle is composed of three layers: the outer and inner layers are lamellate, while the middle one is granulate. This new cycad leaf is compared with similar fossil leaves from Gondwana and Europe/North America, and also with similar extant cycad leaves. Based on the general morphology and the main characters of the cuticle, R. chiguoides is assigned to the family Zamiaceae; moreover it is more closely related to the living Zamia (Chigua) restrepoi (D. Stevenson) Lindstrom than to any other member of the Cycadales. Paleophytogeographic evidence suggests a South American origin of Zamia/Chigua and a further migration to northern latitudes. This new type of leaf also suggests the putative existence of a Chigua clade that may be traced back to the Early Cretaceous when two cycadalean families, Zamiaceae and Stangeriaceae, were already well-established in Patagonia.